Intensification and Deintensification Expressed Through Hyperbola in English Novels (Scientific journal of the Fergana State University, 2025)
This study examines the linguistic features of intensification and deintensification expressed through hyperbolic language in English novels, focusing on how authors manipulate hyperbole to amplify or diminish emotional and thematic elements. By analyzing both historical and contemporary works, the research identifies recurring patterns in the deployment of hyperbole, suggesting that it serves as a crucial rhetorical tool for emotional engagement and thematic resonance. The findings contribute to a deeper understanding of how hyperbole operates within narrative structures to shape reader perception.